Late Gestation Maternal Nutrition Has a Stronger Impact on Offspring Liver Transcriptome than Full-Gestation Supplementation in Beef Cattle - Guilherme Henrique Gebim Polizel; Maria Elis Perissin dos Santos; Aline Silva Mello Cesar; Wellison J. S. Diniz; German D. Ramírez-Zamudio; Paulo Fantinato-Neto; Arícia Christofaro Fernandes; Barbara Carolina Teixeira Prati; Édison Furlan; Gabriela do Vale Pombo; Miguel Henrique de Almeida Santana (Veterinary Sciences)
Maternal nutrition’s impact on liver transcriptome in beef cattle offspring is still underexplored. We investigated the long-term effects of maternal nutrition strategies on the liver transcriptome of pre-slaughter Nelore bulls. Pregnant cows were divided into three groups, each receiving different nutritional regimens: NP (control, only mineral supplementation), PP (late gestation protein–energy supplementation), and FP (protein–energy supplementation throughout pregnancy). Liver samples were collected from male offspring aged 22.5 ± 1 months and analyzed using RNA-Seq (n = 5 per treatment). Principal component analysis (PCA) and differential gene expression analysis were carried out in an R statistical environment. Genes were considered significant when FDR < 0.05. The over-representation analysis (ORA) was performed using the clusterProfiler package from R. Metabolic pathways were considered significant when the Q-value < 0.1. The PCA showed overlapping clusters among the groups. We identified 16 differentially expressed genes (DEGs) associated with PP × NP contrast, four with FP × NP, and two with FP × PP. The ORA revealed two significant pathways (thiamine and butanoate metabolism). The identified genes and pathways were associated with vitamins, energy, oxidative metabolism, and immune function. This study emphasizes the more significant long-term effects of the PP treatment on the offspring’s liver transcriptome compared to the FP treatment.